Learning with owls: Human–wildlife coexistence as a guide for urban design - Dan Parker; Kylie Soanes; Stanislav Roudavski (People and Nature)
Abstract Urban encroachment increasingly threatens wildlife survival and well‐being, underscoring the need for design and management to consider nonhuman species. This article analyses cases of positive coexistence between humans and Powerful Owls (Ninox strenua) to identify key challenges, opportunities, objectives and practical strategies for urban planning. As a species historically linked to old‐growth forests, powerful owls now inhabit urban environments but face significant human‐induced pressures, including diminishing numbers of nesting sites. To explore the potential for positive coexistence, we conducted 10 in‐depth interviews with 19 individuals experienced in observing and advocating for powerful owls. These interviews took place either online or during guided walks through owl habitats in Australian cities. This approach allowed us to supplement existing scientific research, highlight future research areas and document human–owl interactions across three themes. First, participants identified barriers to improving coexistence, including insufficient consideration of owls in urban decision‐making, conflicts between human activities and owl conservation, and the need for improved knowledge sharing. Second, participants' experiences demonstrated that greater knowledge of owl behaviour and habitat preferences can play a vital role in fostering positive coexistence. Third, participants provided specific examples of positive coexistence, illustrating how and why people form relationships with urban wildlife. Building on these findings, we propose urban management strategies that incorporate contributions of nonhuman stakeholders, empowering them to influence decision‐making. Such strategies can promote positive coexistence, facilitate knowledge exchange and guide informed actions. This research can provide valuable guidance for land managers, conservationists, policymakers, ecologists, designers and researchers in environmental humanities working to create inclusive, more‐than‐human urban environments. This guidance includes (a) methods for integrating nonhuman stakeholders into design, planning, management and development processes; (b) approaches to redefining landscape features as catalysts for positive human–wildlife interactions; and (c) examples of technical systems that enhance information flow among stakeholders, encouraging innovation, the adoption of new solutions and accountability. Read the free Plain Language Summary for this article on the Journal blog.